CHALLENGING THE RHETORIC OF CHOICE IN PRENATAL SCREENING - Seavilleklein, Victoria (Bioethics, 2009)
Prenatal screening, consisting of maternal serum screening and nuchal translucency screening, is on the verge of expansion, both by being offered to more pregnant women and by screening for more conditions. The Society of Obstetricians and Gynaecologists of Canada and the American College of Obstetricians and Gynecologists have each recently recommended that screening be extended to all pregnant women regardless of age, disease history, or risk status. This screening is commonly justified by appeal to the value of autonomy, or women's choice. In this paper, I critically examine the value of autonomy in the context of prenatal screening to determine whether it justifies the routine offer of screening and the expansion of screening services. I argue that in the vast majority of cases the option of prenatal screening does not promote or protect women's autonomy. Both a narrow conception of choice as informed consent and a broad conception of choice as relational reveal difficulties in achieving adequate standards of free informed choice. While there are reasons to worry that women's autonomy is not being protected or promoted within the limited scope of current practice, we should hesitate before normalizing it as part of standard prenatal care for all.